English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Step-by-step please...keep getting 28/6.... What am i doing wrong?

2 - 3x = 8(5 - x) - (x - 10)

2007-01-09 05:06:38 · 11 answers · asked by James A 1 in Science & Mathematics Mathematics

11 answers

*Eliminate parenthesis: use distribution > multiply 8 with both terms in the parenthesis >

2 - 3x = 8(5) - 8(x) - (x - 10)
2 - 3x = 40 - 8x - (x - 10)

*Distribute the negative sign with both terms in the parenthesis >

2 - 3x = 40 - 8x - x - (-10)
2 - 3x = 40 - 8x - x + 10
2 - 3x = 50 - 9x

First: combine "like" terms > add 9x to both sides (opposite sides means opposite side) >

2 - 3x + 9x = 50 - 9x + 9x
2 + 6x = 50

Sec: subtract 2 from both sides >

2 - 2 + 6x = 50 - 2
6x = 48

Third: solve for "x" by isolating it on one side > divide both sides by 6 >

6x/6 = 48/6
x = 8

2007-01-09 05:16:41 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

The key to solving problems like this is keeping track of the signs as well as the numbers.

Start with your equation:

2 - 3x =8(5 - x) - (x - 10) Do all the multiplication, then the addition and subtraction. Watch for the sign change to + on the 10

2 - 3x = 40 - 8x - x + 10 Now simplify:
2 - 3x = 50 - 9x Take the variable to one side, and numbers on the other side of the equation:

9x -3x = 50 - 2 Simplify again:

6x = 48 Divide both sides by 6:

x = 8

2007-01-09 13:27:41 · answer #2 · answered by nammy_410 2 · 0 0

2 - 3x = 8(5 - x) - (x - 10)

Multiply the 8 through:

2 - 3x = 40 - 8x - (x - 10)

Get rid of the parentheses (minus a minus is a positive, etc.). This might have been where you made a mistake.

2 - 3x = 40 - 8x - x + 10

Combine the like terms on the right-hand side:

2 - 3x = (40 + 10) + (-8x - x)
2 - 3x = 50 + (-9x)
2 - 3x = 50 - 9x

Now try to isolate x. Subtract 2 from both sides so that we only have "x" terms on the left.

2 - 3x = 50 - 9x
- 3x = 48 - 9x

Add 9x to both sides so that there are no "x" terms on the right:

-3x + 9x = 48 + 9x - 9x
6x = 48 + 0
6x = 48

Finally, divide both sides by 6. You get x=8.

2007-01-09 13:18:58 · answer #3 · answered by Anonymous · 0 0

2 - 3x = 8(5 - x) - (x - 10)
First distribute 8(5 -x)
2 -3x = 40 -8x -(x -10)
Mutiply (x - 10) by -1 to distribute "-" sign.
(x -10)*-1 = x*-1 -10*-1 = -x + 10
2 -3x = 40 -8x -x +10
Move all x terms to left side
2 -3x +8x +x = 40 -8x + 8x -x +x +10
2 -3x +8x +x = 40 + 10
Move 2 to the right side
2 -2 -3x +8x +x = 40 + 10 -2
-3x +8x +x = 40 + 10 -2
Add
6x = 48
Divide by 6
x = 48/6
x = 8.
Check
2 - 3*8 = 8*(5-8) - (8 -10)
2 - 24 = 8*-3 - (-2)
-22 = -24 + 2
-22 =-22

2007-01-09 13:20:15 · answer #4 · answered by Edgar Greenberg 5 · 0 0

2 - 3x = 8(5 - x) - (x - 10)

2 - 3x = 40 - 8x - x + 10

2 - 3x = 50 - 9x

2 - 3 + 9x = 50 - 9x + 9x

2 + 6x = 50

2 + 6x - 2 = 50 - 2

6x = 48

6x/6 = 48/6

x = 8

The answer is x = 8

Insert the x value into the equation

- - - - - - - - - - - - - - - - - - - - - - -

Check

2 - 3x = 8(5 - x) - (x - 10)

2- 3(8) = 8(5 - 8) - (8 - 10)

2 - 24 = 8(- 3) - (- 2)

- 22= - 24 + 2

- 22 = - 22

- - - - - - - - -s-

2007-01-09 14:01:04 · answer #5 · answered by SAMUEL D 7 · 0 0

2- 3x = 8(5-x) - (x-10)
Let's get rid of the parentheses by multiplying it out, so you get

2- 3x = 40 - 8x - x + 10

(That last - (x - 10) is like -1(x-10), in case you didn't know.
Okay, so now we move all the x's to one side and all the numbers to the other

-3x + 8x +x = 40 + 10 - 2

Add them and you get 6x = 48
Divide both sides by 6 and you get x = 8

2007-01-09 13:16:10 · answer #6 · answered by theyuks 4 · 1 0

2 - 3x = 8(5 - x) - (x - 10)
2 - 3x = 40 - 8x - x + 10
- 3x + 8x + x = 40 + 10 - 2
6x = 48
x= 48/6
x= 8
I hope this helps!!

2007-01-09 13:17:14 · answer #7 · answered by smart-crazy 4 · 0 0

#1 problem with all math students:

Failure to distribute the minus sign when multiplying

You're probably doing this:

2-3x=40-8x-x-10

the last term should be +10, not -10 since a negative times a negative is a positive.

2007-01-09 13:21:46 · answer #8 · answered by bequalming 5 · 0 0

2 - 3x = 8(5 - x) - (x - 10)
2 - 3x = 40 - 8x - x + 10
- 3x + 8x + x = 40 + 10 - 2
6x = 48
x= 48/6
x= 8

2007-01-09 13:12:49 · answer #9 · answered by Rockie 1 · 3 0

2 - 3x = 8(5-x) - (x - 10)
2 - 3x = 40 - 8x - x + 10
2 - 40 - 10 = -8x -x + 3x
-48 = -6x
8 = x

x = 8

2007-01-09 13:14:57 · answer #10 · answered by Donny Dutch 4 · 1 1

fedest.com, questions and answers